1999
DOI: 10.1159/000016547
|View full text |Cite
|
Sign up to set email alerts
|

Plaque pH and Associated Parameters in Relation to Caries

Abstract: Intensified plaque acidogenicity in caries–prone subjects was reported many years ago, but emerging evidence has suggested that the relationship may not be as strong as once thought. We have now determined a range of acidogenicity variables in subjects having both caries prevalence and incidence data, and have included plaque mineral data in the analysis. pH measurements were made in 20 randomly selected subjects from a high–caries group (mean DMFS = 8.95) and 20 from a caries–free group of Beijing children ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
0
5

Year Published

2004
2004
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 29 publications
0
50
0
5
Order By: Relevance
“…34 Children had been asked not to eat or drink for 3 h before the measurements. The measurement was only performed if the electrode was inserted into the biofilm.…”
Section: Dental Plaque Ph Measurementmentioning
confidence: 99%
“…34 Children had been asked not to eat or drink for 3 h before the measurements. The measurement was only performed if the electrode was inserted into the biofilm.…”
Section: Dental Plaque Ph Measurementmentioning
confidence: 99%
“…In other words, pH could be one of the factors that determine locale-specific gene expression patterns, since certain body sites are characterized by variations in pH from the homeostatic 7.4 ( Fig. 6) (5,10,16,21,22,31,41,53). Given the breadth of the MAS, plus the fact that the intracellular pH is maintained within very narrow limits, the pH differential must be sensed by one or more surface receptors and transduced to the interior of the cell.…”
Section: Discussionmentioning
confidence: 99%
“…There is no simple relationship between the concentration of fl uoride ions in plaque and microbial acid production. Vogel et al [2002] reported no correlation between fl uoride levels in plaque and lactic acid formation while Dong et al [1999] also found no differences in the concentration of acidsoluble fl uoride ions in the plaque of caries-free and highcaries groups of subjects.…”
Section: Discussionmentioning
confidence: 96%